Chaotropic anion based "water-in-salt" electrolyte realizes a high voltage Zn–graphite dual-ion battery. Issue 4 (12th January 2022) - Zafar, Zahid Ali; Abbas, Ghulam; Knizek, Karel; Silhavik, Martin; Kumar, Prabhat; Jiricek, Petr; Houdková, Jana; Frank, Otakar; Cervenka, Jiri
Abstract : We report a high voltage Zn–graphite dual-ion battery based on Zn(ClO4 )2 water-in-salt (WiS) electrolyte with a wide electrochemical window of 2.80 V and high oxidative stability of 2.60 V vs. Zn/Zn 2+ . Abstract : Aqueous Zn-based batteries are promising candidates for grid energy storage due to their low cost, intrinsic safety, and environmental friendliness. Nevertheless, they suffer from limited energy density due to the utilization of low-voltage cathodes and electrolytes. Graphite could be a viable high-voltage cathode material owing to its high redox potential (2.1–3.1 V vs. Zn/Zn 2+ ). However, finding a suitable aqueous electrolyte with high anodic stability remains a fundamental challenge. This work realizes a high-voltage and low-cost aqueous Zn–graphite dual-ion battery based on a Zn(ClO4 )2 water-in-salt electrolyte with a wide electrochemical window of 2.80 V. The implementation of the supersaturated Zn(ClO4 )2 water-in-salt electrolyte containing strong chaotropic ClO4 − anions expands the oxidative stability of the aqueous electrolyte beyond 1.65 V vs. Ag/AgCl or 2.60 V vs. Zn/Zn 2+, and facilitates reversible plating/stripping of Zn 2+ with a low overpotential of <50 mV at 1 mA cm −2 and a high upper cut-off potential of 2.5 V vs. Zn/Zn 2+ . Consequently, the Zn–graphite dual-ion battery delivers a maximum discharge capacity of 45 mA h g −1 at 100 mA g −1 with a mean discharge voltage of ∼1.95 V and cycle life of over 500 cycles.